Applications of ALD MnO to electrochemical water splitting1. Issue 21 (7th June 2015) - Pickrahn, Katie L.; Gorlin, Yelena; Seitz, Linsey C.; Garg, Aaron; Nordlund, Dennis; Jaramillo, Thomas F.; Bent, Stacey F.
<x xml:space="preserve">Abstract</x> The effect of OER potentials on the oxidation and morphology of ALD-MnO electrocatalysts is investigated with an emphasis on applications.